Menganalisis Tindak Tutur Ekspresif dalam Film Miracle In Cell No.7 - Priscillia Febrianty Purba; Agustina Verawati Simorangkir; Nadia Saputri Daulay; Ovi Oktavia Kresensia Sihombing; Egina Shinta Bella Br Ginting Marina Gab; Anggia Puteri (Departement of Mathematics Education, 2024)
This research aims to analyze the expressive speech acts contained in the film Miracle in Cell No. 7. Expressive speech acts are a form of verbal communication that is used to express the speaker's emotions, feelings or attitude towards a situation. Through a pragmatic approach, this research identifies the types of expressive speech acts that appear in dialogue between characters and how these speech acts reflect the interpersonal relationships and emotions of the characters. Data was taken from conversations in the film which were then analyzed qualitatively. The research results show that expressive speech acts in this film reflect various forms of emotions such as happiness, sadness, gratitude and empathy which play an important role in character development and storyline. This research provides insight into how language is used to express feelings in film contexts and enriches understanding of the pragmatic function of language in popular media.